The Effect of Corporate Social Responsibility On the Relationship Between Corporate Reputation and Brand Equity – A Study of GSM Users - Güneş, Özlem Öncel; Gözükara, İzlem and Uludağ, Candide (European Scientific Journal, ESJ, 2020)
Corporate reputation refers to stakeholder perception of a company. All companies desire a strong and favorable reputation as it is an effective means to brand loyalty and a competitive edge. Building a strong reputation requires reputation management, which is often based on sustainability and consistency as well as creating an emotional bond with consumers. This has led many companies to be more involved in the social responsibility initiatives since such initiatives are known to change consumer’s beliefs and attitudes toward brands. From this perspective, the present study aims to investigate the mediating role of corporate social responsibility in the relationship between corporate reputation and brand equity perceptions. The study sample consisted of 324 GSM users in Turkey. The data was collected using survey method and analyzed using SPSS 23.0 statistical package. The results of the study showed that corporate reputation has a positive effect on brand equity and corporate social responsibility plays a mediating role in this relationship.